The interactive effects of religiosity and recognition in increasing donation - Felix Septianto; Fandy Tjiptono; Widya Paramita; Chiew, Tung Moi (Emerald Publishing Limited, 2021)
Purpose: The purpose of this paper is to examine a three-way interaction between the two motivational orientations of religiosity (i.e. intrinsic and extrinsic) and recognition (in this study, an explicit expectation that behavior is recognized) on charitable behavior. Further, drawing upon the evolutionary psychology perspective, the status motive is predicted to mediate the predicted effects. Design/methodology/approach: Three experimental studies were conducted using a 2 (intrinsic religiosity: low/high; measured)2 (extrinsic religiosity: low/high; measured)2 (recognition: yes/no; manipulated) between-subjects design to examine the predicted effects on likelihood to donate and donation allocations in two Asian countries, namely, Indonesia and Malaysia. Findings: The results show that recognition increases charitable behavior among consumers with a high level of extrinsic religiosity but low level of intrinsic religiosity (Studies 1a, 1b and 2). Further, a status motive mediates the predicted effects (Study 2). Research limitations/implications: The present research provides a novel perspective on how marketers can purposively use recognition in charitable advertising to encourage charitable behavior among religious consumers – but only in Asia. Practical implications: This paper presents the case for how a non-profit organization can develop charitable advertising for disaster relief in Indonesia (Studies 1a and 1b) and Malaysia (Study 2). The findings of this research could potentially be extended to other organizations in Asia or other countries where religiosity places an important role in consumer behavior. Originality/value: This research shows the interactive effect between extrinsic religiosity, intrinsic religiosity and recognition can increase charitable behavior in Asia.